Physical Activity and Nutrition Programs at the Kansas Department of Health and Environment - Johnson, Bethany Paige (My University, 2013)
Kansas Department of Health and Environment The Kansas Department of Health and Environment (KDHE) is a state level department concerned with protecting and improving the health and environment of all Kansas residents (Kansas Department of Health and Environment, 2011). KDHE is directed by the Secretary and State Health Officer, Dr. Robert Moser, and is divided into four separate divisions. The four divisions are Administration-Office of the Secretary, Division of Public Health, Division of Health Care Finance and Division of Environment (Kansas Department of Health and Environment, 2011). Division of Health The Division of Health encompasses nine separate bureaus and is responsible for a large variety of tasks. This division overseas topic areas ranging from developing ways to provide communities with access to public health, primary care, and prevention services to managing the state civil registration system (births, deaths, marriages, divorces). Other tasks include investigating disease outbreaks and finding ways to prevent the spread of disease, licensing facilities that provide care to people (daycares, preschools, hospitals, foster homes, etc.), and educating the public on injury prevention and chronic diseases. Bureau of Health Promotion The Bureau of Health Promotion (BHP) aims to improve the quality of life and prevent chronic disease, injury, and premature death for all Kansas residents. This is done through partnerships that promote healthy behaviors, policies, and environmental changes. Specifically the BHP is responsible for functions related to reducing the preventable burden of chronic disease and injuries. Currently 75% of all health care expenditures in Kansas are a result of chronic disease and injuries are the leading cause of death in Kansas for individuals aged 1-44 (Kansas Department of Health and Environment, 2012). The Bureau of Health Promotion consists of nine programs/sections covering a range of public health topics including: healthy communities, schools, tobacco prevention, physical activity and nutrition, injury prevention, and chronic disease prevention and early detection (Health Promotion, 2013).
Keywords: Farmer's Market; Nutrition Program; Public Health; Public Health (0573)